The Persistence of the Accounting Policies After the Transition to IFRS of the Romanian Listed Companies - Costel Istrate (Journal of Accounting and Management Information Systems (JAMIS), 2015)
The study aims to analyse the accounting policies chosen by Romanian listed companies during the mandatory transition to IFRS in their individual accounts (starting with 2012). Following particularly Kvaal and Nobes (2010), we propose the general hypothesis of a continuation of the main accounting policies already in use in the Romanian national accounting, to the extent that they are compliant with IFRS. The data collected for about 80 firms allow us to conclude that this general assumption is widely confirmed. The items analysed relate to the statement of financial position (format and some other elements), the income statement (several items), the cash flow statement (operating cash flow, dividends and interests), fixed assets (measurement after recognition of PPE, intangibles and investment properties), cost formulas for inventories, dimensions of the financial statements.
Keywords: M41; 650; IFRS; accounting differences; accounting choices; continuation of accounting policies